2016
DOI: 10.1589/jpts.28.2754
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effect of pre- and post-operative physical therapy versus post-operative physical therapy alone on pain and recovery of function after total knee arthroplasty

Abstract: [Purpose] The aim of the present study was to compare the effect of pre-operative and post-operative physical therapy versus post-operative physical therapy alone on pain and recovery of function after total knee arthroplasty. [Subjects and Methods] Fifty patients (18 males and 32 females) ranging in age from 48 to 80 years (mean 63.28, SD 9.44) participated in a 6-week two-arm randomized rater-blinded trial. One group received pre- and post-operative physical therapy whereas the other group received only post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Among the rest 50 studies, 31 studies were excluded, which was attributed to several factors. Lastly, 19 full-text articles were applicable to the present meta-analysis [ 8 11 , 14 28 ] (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the rest 50 studies, 31 studies were excluded, which was attributed to several factors. Lastly, 19 full-text articles were applicable to the present meta-analysis [ 8 11 , 14 28 ] (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Pain was measured by VAS scores. Six studies [ 8 , 14 , 15 , 21 , 26 , 28 ] (317 patients) reported the effects of pre-habilitation on postoperative pain. In this study, data were extracted twice.…”
Section: Resultsmentioning
confidence: 99%
“…Reasons for exclusion included: 1) Abstract/Title only (e.g., conference proceedings), 2) Duplications, 3) Continuous Passive Motion, 4) Study not yet published, 5) Study terminated, 6) Wrong intervention, study design, or patient population, and 7) Unable to locate/translate study. Finally, 112 RCTs were included in this review [ 18 24 , 26 – 130 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Research shows that physical therapy (PT) before a procedure does not appear to influence postoperative outcomes. 22 In a cohort study, Valencia et al 23 found no evidence of benefit for preoperative PT on postoperative PT treatment length or postsurgical outcomes. If patients do not undergo preprocedure PT, physical therapists should provide preoperative teaching, including gait, walker, and exercise instruction, and should identify patients' needs at home.…”
Section: Physical Therapymentioning
confidence: 98%
“…Research shows that physical therapy (PT) before a procedure does not appear to influence postoperative outcomes . In a cohort study, Valencia et al found no evidence of benefit for preoperative PT on postoperative PT treatment length or postsurgical outcomes.…”
Section: Perioperative Protocolsmentioning
confidence: 99%